ANALISA SWOT KEBERHASILAN USAHA PADA PRODUK PEWANGI LAUNDRY “MJL” (STUDI PADA TOKO HAYYU BERKAH DI CIKARANG SELATAN) - Biaggi Armanda Susilo; RR. Wening Ken Widodasih; Kurbandi Satpatmantya BR (LPPM Institut Pendidikan Nusantara Global, 2023)
Laundry perfume is a liquid with a chemical base made from a variety of mixed ingredients that can be used to scent clothes. With a wide determination of fragrance fragrances to perfume the clothes of the clothes. The laundry at the laundry is dominated by this fragrance. Even when opened from the packaging, the scent of the clothes is completely absorbed and when worn it will feel refreshing. This laundry perfume can be used to scent washed clothes when they are washed, when they are ironed by spraying, and when they are packed. Please note that the perfume used in all three processes must be the same. This study aims to analyse the Swot Analysis of Business Success in Laundry Fragrance Products